Linearisierungsmöglichkeiten und Kasuszuweisung in deverbalen Nominalphrasen. Ein deutsch-polnischer Vergleich - Aptacy, Jarosław (Wydawnictwo Naukowe UAM, 2010)
In the following paper German and Polish deverbal noun phrases will be examined in respect to the linearization of their constituents. The point of departure will be the adjacency condition which is obligatory in the Genitive DPs in German, but optional in Polish. In other words, Polish displays more linearization possibilities than German. In addition to adjacency which is conditioned by grammar also communicative factors and text grammar condition the linearization of DPs. Constituents with a higher comment value tend to appear as far to the right of the deverbal noun as possible, while topic constituents stand closer to the noun.
Linearization and case assignment in deverbal noun phrases. A comparison of German and Polisch
Keywords: noun phrase; adjacency; Genitive; Linearization of DPs